Association Between Parental Gender-Equality Attitudes and Reported Support for Girls’ Education: Evidence from a Rural Indonesian Village - Sheila Naovallia; Leni Anggraeni; Sehan Rifky Arfanaldy (Journal of Pedagogy and Education Science, 2026)
Parents’ gender-equality attitudes may be associated with the support they report providing for girls’ education. This article presents an exploratory reanalysis of de-identified data from a 2021 cross-sectional survey of 145 parents of school-age daughters in Waleddesa Village, Indonesia. It examined the association between parental gender-equality attitudes and reported support for girls’ education. Gender-equality attitudes were measured using five Likert-type items, whereas reported educational support was measured using three Likert-type items. Spearman’s rank correlation was specified as the primary analysis, with Pearson correlation and simple linear regression reported as supplementary analyses. The findings showed a positive association between parental gender-equality attitudes and reported support for girls’ education (Spearman’s rho = 0.600, p < 0.001; Pearson’s r = 0.552, p < 0.001). The supplementary regression model was statistically significant, F(1, 143) = 62.560, p < 0.001, and accounted for 30.4% of the variation in reported support. Parents strongly endorsed the importance of education for children’s futures, whereas endorsement of girls’ access to higher-status careers was comparatively lower. This pattern suggests that support for education may coexist with reservations about women’s future social and economic roles. The findings should be interpreted as exploratory because the data were cross-sectional, self-reported, and based on short scales with limited construct-specific internal consistency. The study contributes rural Indonesian evidence that gender-equitable parental attitudes and stronger reported support for girls’ education tend to co-occur.